Social Capital Derification in Islamic Economy (Study of Street Vendors in Makassar) - Madjid, St. Saleha; Mustika, Mega (Universitas Muhammadiyah Makassar, 2022)
Islam places a great emphasis on being able to protect and maintain life. This issue is in line with the objectives of Islamic law (maqasid al-shari'ah). The purpose of the Islamic law is to benefit servants (humans) in this life and the hereafter. This study describes the features of Islamic economics on social capital and how the dynamics of street vendors in an Islamic economic perspective can strengthen social capital as a merchant survival strategy, namely the value of ta'awun (helping each other)., and ukhuwah (brotherhood), ihsan (kindness), and leadership. It will also discuss how Islamic-based social capital can be a survival strategy for informal businesses in Makassar. The research was conducted at the Makassar Central Market from 12 informants. The result of this research is that the basic values of Islamic economics, such as ummah wahidah, ukhuwah, ta'awun, ihsan, and al-is al-adalah, become social capital that is are able to move traders to fight together to solve problems and meet their needs.